The impact of top management's environmental responsibility audit on corporate environmental investment: evidence from China. Issue 7 (3rd September 2020) - Zeng, Changli; Zhang, Lu; Li, Jiangtao
Abstract : Purpose: The purpose of this paper is to examine the effect of top management's environmental responsibility audit (ERA) implementation on firms' investment for environmental protection in China. Design/methodology/approach: The sample comprises firms publicly traded on A-Share in China from 2011 to 2017. The authors used the ordinary least squares regression model to test the relation between ERA implementation and corporate environmental investment. Findings: Firms' environmental investment increases significantly after the ERA implementation. Compared to state-owned enterprises (SOEs), non-state-owned enterprises (non-SOEs) are more likely to increase their environmental investment after ERA implementation. Moreover, such change is more likely for non-heavily polluting enterprises (non-HPEs) compared to heavily polluting enterprises (HPEs). Practical implications: This paper provides an in-depth analysis of the positive influence of environmental enforcement on corporate behavior, which could serve as reference for regulators on the latest environmental accounting practice in China and other emerging economies. Social implications: This paper shows that clear assignment of environmental responsibility and subsequent assessment of environmental performance are contributing factors to effective and efficient implementation of an environmental management system. Originality/value: Contributing to accounting and environmental management literature, this paper explains how mandated environmental audit incentivizes firms to deal with environmental issues. Because there is no prior research concerning the mandatory implementation of environmental audit in China, this paper is of high-innovatory value by providing a better understanding of environmental auditing and providing an economic explanation for government intervention as an effective means of mitigating environmental degradation in emerging economies.